2002
DOI: 10.1080/jmf.11.3.176.182
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the factor V, prothrombin and MTHFR genes are not risk factors for recurrent fetal loss

Abstract: Our study did not demonstrate that women who are carriers of the factor V, prothrombin, or MTHFR mutations are at higher risk of recurrent fetal loss than women without these mutations. In regards to factor V Leiden, the prevalence in our cases (1.7%) was not statistically different from the known population prevalence of 5%. However, the high prevalence in our controls (14%) was unusual. Factor V Leiden may protect against bleeding in early pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…In the studies by Souza et al [44] and Foka et al [58], PTG was significantly more common among cases. The difference of the mutation reported by Dilley et al [74] did not reach statistical significance. However, Dilley et al used a study group with a history of all trimester losses and Foka et al used a study group with only first or second trimester losses.…”
Section: Review Of the Selected Articlesmentioning
confidence: 87%
See 3 more Smart Citations
“…In the studies by Souza et al [44] and Foka et al [58], PTG was significantly more common among cases. The difference of the mutation reported by Dilley et al [74] did not reach statistical significance. However, Dilley et al used a study group with a history of all trimester losses and Foka et al used a study group with only first or second trimester losses.…”
Section: Review Of the Selected Articlesmentioning
confidence: 87%
“…Finally, the study performed by Dilley et al [74] reported a remarkable high prevalence of the factor V Leiden mutation in the controls: 14.1% as compared to 1.7% in the cases, which was a significant difference. Many factors were matched for among cases and controls, including BMI, smoking, hypertension, education and history of thrombosis.…”
Section: Review Of the Selected Articlesmentioning
confidence: 87%
See 2 more Smart Citations
“…It concluded that testing for these mutations in the initial screening of women with RPL and negative personal thromboembolic history was not cost-effective (Serrano et al, 2011). Similarly, in a controlled study, Dilley et al found the frequency of FVL to be similar in 60 women with RPL and 92 controls without a history of miscarriage (Dilley et al, 2002).…”
Section: Discussionmentioning
confidence: 98%